Split-hand phenomenon in motor neuron diseases: Sonographic assesment of muscle thickness. Issue 8 (August 2020) - Abraham, Alon; Fainmesser, Yaara; Drory, Vivian E; Bril, Vera
Highlights: Split hand index determined by sonography can aid in ALS and spinal muscular atrophy (SMA) diagnosis. Split hand index determined by sonography is superior to abductor pollicis brevis/abductor digiti minimi and thenar index. Thenar index determined by sonography is not useful for SMA diagnosis. Abstract: Objective: To explore the diagnostic accuracy of the split-hand index (SHI) for amyotrophic lateral sclerosis (ALS) and spinal muscular atrophy (SMA) using sonographic assessment of muscle thickness. Methods: We performed a prospective sonographic assessment of hand muscle thickness in 59 controls, 87 patients with ALS, and 33 patients with SMA. We determined the diagnostic accuracy of SHI for differentiating patients with ALS and SMA from controls. Results: Patients with ALS and SMA had significantly lower muscle thickness and SHI values compared with controls. SHI showed excellent diagnostic accuracy for differentiating ALS from controls, and good diagnostic accuracy for differentiating SMA from controls. Conclusions: SHI determined by sonographic measurement of hand muscle thickness seems to be a promising tool for the diagnosis of ALS and may be added easily when performing neuromuscular ultrasound. Significance: SHI determined by sonographic measurement of hand muscle thickness can differentiate between healthy subjects and patients with ALS and SMA.